Análise da modelagem da informação da construção (BIM) em processos de projetos industriais - Ezequiel Rosa Dias (2015)
This study aims to investigate the elaboration of digital models and the design process of industrial buildings by a group of companies from Belo Horizonte, using mostly BIM and industrial parametric modeling software. An exploratory research was conducted through unstructured interviews, documentation and information analysis provided by the studied group. Our findings show that the companies use 3D modeling mainly for visualization and spatial interferences checking between disciplines. Presently these companies are focused on solving data exchange problems due to the simultaneous use of BIM and industrial parametric modeling tools. It is important to note that this practice can stimulate the use of new technologies by AEC sector as it systematically develops more complex designs. The interoperability between the applied tools occurs via direct links, proprietary formats and an isolated case of public format. It was noted that the group´s preference for proprietary formats occurs due to the slow pace of public standards developers at solving technological overlapping issues. This fact requires harmonization initiatives between the different sectors involved, especially between standards such as IFC, CIS/2 and ISO-15926. It was possible to verify that, at the end of the modeling phase, each team of the studied group has its own three-dimensional parameterized digital model. However, the integration of these interdisciplinary models, which is performed via physical server in a network, does not carry out sufficient parametric features to simulate the whole enterprise. Regarding the design process, it was noted that some phases (conceptual, basic and detailed) are developed sequentially. There is, however, some concurrency between the design phases and the materials and 3D model management steps. We observed some interdisciplinary collaboration and parallelism between activities of a same design stage. The design sequential characteristics may indicate that the BIM or industrial parametric modeling have not yet encompassed the entire design process towards the integration of the steps. This finding can be enhanced by the use of 2D/3D non-parameterized software by some disciplines in the conceptual and basic design stages. In relation to the materials and automation projects" management, the companies have adopted their own tool, used for creation of parametric objects families, translation of digital models between non-interoperable tools and to compile bills of materials for purchase. It is noteworthy that the need for skilled labor and high costs for developing proprietary standards, however, confer exclusivity to companies that use them. In this sense, designers with scarce resources will be induced to use interoperability standards from software developers, risking to become their hostages, a practice that tends to monopolize markets. In this sense, the participation of universities and the public sector becomes relevant in promoting partnerships with the private sector with the aim of developing open standards for the dissemination of knowledge in the area.